Microchannel interrogation with twyman-green interferometer - Wan Mokhdzani, Wan Nor Haimi
The Twyman-Green Interferometer (TGI) setup for measuring microfluidic channel depth has been developed. The main objective of this study is to develop a non-contact measuring instrument capable of performing depth measurements of a microfluidic channel made of silica wafer. The microfluidic channel is fabricated using the photolithography process and reactive ion etching. Microfluidic channel depth has been measured with the Twyman-Green Interferometer setup. The interferometer setup relies on the optical path length change caused by the rotating transparent silica reference sample in one of its arms. Intensity of fringes produced by the interferometer is detected and recorded with a corresponding photodiode. The intensity results are plotted against the optical path variation of the reference sample which causes an optical path difference in the reference arm. Depth measurement of the microfluidic channel has been extracted from the optical path difference obtained from the interferometer setup. Transparent silica reference samples with etched thickness of 0.681 μm (Ref 1), 1.396 μm (Ref 2) and 2.102 μm (Ref 3) has been used to investigate and determine which is the most accurate reference sample to be used in determining depth of microfluidic channel. Depth of microfluidic channel obtained from Twyman-Green Interferometer has been compared to depth results obtained from atomic force microscopy and surface profilometer. Applying Ref 1, Ref 2 and Ref 3 as rotating reference samples yielded 94.45 %, 84.76 % and 66.97 % compliance with measured depth obtained from surface profilometer. Although there are slight variations with results obtained from surface profilometer and atomic force microscopy, the experimental results proves that the Twyman-Green Interferometer is able to determine microfluidic channel depth and etched depth of thin Si samples. Resolution of the TGI setup is 0.27 μm and is suitable to measure depth profiles ranging from 0.27 μm to 5 μm. Therefore, the modified TGI setup in this research is suitable for measurements of depths or thickness profiles ranging from 0.27 μm to 5 μm with a fringe visibility of more than 0.5.